High-resolution characterization of the development and decay of seasonal hypoxia in the Gulf of Riga, Baltic Sea - Liblik, Taavi; Stoicescu, Stella-Theresa; Buschmann, Fred; Lilover, Madis-Jaak; Lips, Urmas (Frontiers in Marine Science, 2023)
The Gulf of Riga is a shallow basin in the eastern Baltic Sea connected to the Central Baltic Sea via shallow straits. Seasonal oxygen depletion occurs in the deep layer of the gulf. We conducted hourly measurements of dissolved oxygen, temperature, and salinity in the deep layer (50 m) of the gulf and observed the full cycle of development and relaxation of hypoxia in 2021. Hypoxia (<2.9 mg l-1) first occurred on 27 June and was observed for 71 days until its complete decay on 22 October. Average oxygen decline of 0.10 mg l-1 d-1 from saturation in mid-April until mid-July and 0.04 mg l-1 d-1 onwards until the end of August were observed. This seasonal pattern was superimposed by short-term variability in time scales from hours to days and was probably caused by inertial oscillations, (sub)mesoscale processes, deep layer currents, and pycnocline movements. Ventilation events with a relatively low impact and duration of up to ten days occurred in the deep layer due to the inflows of the saltier water from the Central Baltic. The inflowed water originated from the upper layer in winter and the thermocline in summer and was almost saturated in oxygen. Mostly mixing with existing oxygen-depleted water in the Gulf of Riga, but also local consumption declined the oxygen levels in the inflow water before it arrived at the observing station. Monthly standard deviations in oxygen varied from 0.3 to 2.8 mg l-1 and illustrated the added value of Eulerian measurements to complement the conventional monitoring.